The Legal System of Scotland as a Hybrid Legal System - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2023)
This scientific article analyzes the legal system of Scotland, which, as you know, is not subject to English (common) law. The paper addresses the question of which legal family it is a part of.